Decadal Evolution of Landslides in the Siwalik Zone: a Case Study of Babai Watershed, Nepal - Bhandari, Bharat Prasad; Dhakal, Subodh (Journal of Institute of Science and Technology, 2021)
The Siwalik zone of the Nepal Himalaya is highly sensitive to landslides. The study of landslides in the catchment scale gives the basic concept of the overall landslides of the typical zone. In this study, the decadal evolution trend of the four largest landslides of the Babai River watershed was evaluated. The Landsat, Sentinel-2, and Google Earth imageries were used to obtain the physical data of the landslide from 2010 to 2019. The area, total length, and width of scar toe, and the body of landslides were obtained from the images. The rainfall data of two stations was used to evaluate the role of rainfall in the landslide development and evolution process. The trend of rainfall and area of landslides was not the same but the development process of all four landslides was more or less similar. The area of landslides fluctuated till 2014 but suddenly increased after 2015. The landslide area was highest in 2017 and moderately changed in 2018 and 2019. The landslides showed dynamic behavior in a decade with their typical expanding, widening, and reducing characters.